1996
DOI: 10.1042/bj3140027
|View full text |Cite
|
Sign up to set email alerts
|

A cleavage-site-directed inhibitor of interleukin-1β-converting enzyme-like proteases inhibits apoptosis in primary cultures of rat hepatocytes

Abstract: Apoptosis induced in primary hepatocytes by transforming growth factor beta1 and staurosporine produced chromatin condensation, DNA cleavage is detected by in situ end-labelling, field inversion and conventional gel electrophoresis, and cell detachment. These effects were abolished by benzyloxycarbonyl-valinylalanylaspartylfluoromethyl ketone, a cleavage-site-directed inhibitor of interleukin-1beta-converting enzyme-like proteases, and this finding suggests that these enzymes are involved in liver apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 33 publications
6
56
0
Order By: Relevance
“…Pre-treatment of hepatocytes with broad spectrum caspase inhibitor, z-VAD-FMK and more specific inhibition of caspase-3 (Ac-DEVD-CHO or z-DEVD-FMK), caspase-8 (z-IETD-FMK) and caspase-9 (z-LEHD-FMK) has provided evidence in the same way as had been reported in previously studied cell types and cell lines (Cain et al 1996;Jones et al 1998;Blom et al 1999;Woo et al 1999;Albright et al 2003). Similarly, we show in the present study that staurosporine-induced apoptosis can be blocked by treatment with caspase inhibitors.…”
Section: Discussionsupporting
confidence: 74%
“…Pre-treatment of hepatocytes with broad spectrum caspase inhibitor, z-VAD-FMK and more specific inhibition of caspase-3 (Ac-DEVD-CHO or z-DEVD-FMK), caspase-8 (z-IETD-FMK) and caspase-9 (z-LEHD-FMK) has provided evidence in the same way as had been reported in previously studied cell types and cell lines (Cain et al 1996;Jones et al 1998;Blom et al 1999;Woo et al 1999;Albright et al 2003). Similarly, we show in the present study that staurosporine-induced apoptosis can be blocked by treatment with caspase inhibitors.…”
Section: Discussionsupporting
confidence: 74%
“…These results ~dggested that the TLCK target was not part of a common t ffector mechanism but that it had an important function either 1 ositively or negatively regulating apoptosis dependent on the cell type. In contrast the ability of Z-VAD.FMK to inhibit ;'poptosis induced by diverse stimuli in several different systems ( 19,40,44 and the present study] support the hypothesis that ; is inhibiting a common mediator of apoptosis. This common I mediator of apoptosis in both the nematode and mammals ,#ppears to be a ted-3/ICE-like cysteine protease [13-201.…”
Section: Parp Proteolysissupporting
confidence: 80%
“…Cain et al [33] demonstrated that YVAD-CMK inhibited apoptosis of rat hepatocytes induced by transforming growth factor β1 and staurosporine, and these results suggested that an ICE-like protease is involved in the induction of apoptosis in these cells. Given the results with human hepatoma cells in the present study, it is suggested that different apoptotic signals may show different preferences in the activation of caspases.…”
Section: Discussionmentioning
confidence: 99%